Desain dan Analisis Finite Elemen Rangka Gantry Crane Menggunakan Software Autodesk Inventor Profesional 2024 - Al Ichlas Imran; Aminur; I Made Widana (Piston: Jurnal Teknologi, 2024)
Currently, the gantry crane still uses steel material. The steel is protected using a coating paint to minimize the impact of corrosion. However, this method is inefficient given the high rate of corrosion due to its coastal location. This also causes maintenance issues because repainting must be done regularly and periodically. Additionally, not all equipment has annual maintenance funding. The aim of this study is to design and analyze the stress of a 9-ton capacity gantry crane using Aluminium 6061 material. Finite element analysis was conducted using Autodesk Inventor Professional 2024 software. The results of this study indicate that the gantry crane frame is safe to use because the von Mises stress analysis result of 2,778 MPa is still below the yield strength of Aluminium 6061 material, which is 275 MPa. A safety factor of 2.07 shows that the gantry crane design is very safe to withstand loads up to 9 tons.